2015
DOI: 10.1007/s12160-015-9719-y
|View full text |Cite
|
Sign up to set email alerts
|

Illness Schema Activation and the Effects of Illness Seasonality on Accessibility of Implicit Illness-Related Information

Abstract: Background. Research has demonstrated that implicit models of illness can be activated by priming techniques. Purpose. We tested the hypothesis that following a supraliminal? prime for the common cold, illness-related schematic information would be more accessible when the illness is 'in-season' than when it is 'out-of-season'. Methods. A 2(common cold vs. neutral prime) X 2(in-season vs. out-of-season) experimental design. Participants (N=85) were primed prior to completing a modified Stroop color-naming task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Many authors have advocated an integrated theoretical approach [30][31][32][33][34][35][36][37][38] and it has utility in the current context because it allows us to account for beliefs associated with illnesses, which may compel individuals to engage in salient health related behaviors to cope with the threat, and beliefs about actual participation in health-related behaviors. Specifically, illness beliefs are expected serve as distal predictors of behaviors relevant to coping with illness threat, a theoretically-consistent effect that has not only been corroborated by research showing relations between illness representations and coping behaviors across multiple conditions, but also in laboratory research demonstrating that activating cognitive representations of illness through priming [16,39] leads to the activation of related behavioral responses for the illness [40]. Beliefs about behaviors derived from social cognitive models should be more proximal predictors of behavior given the correspondence and specificity of the beliefs to the behavior themselves and the measures used to tap them [41][42][43].…”
Section: About Illnesses and Beliefs About Behaviorsmentioning
confidence: 91%
“…Many authors have advocated an integrated theoretical approach [30][31][32][33][34][35][36][37][38] and it has utility in the current context because it allows us to account for beliefs associated with illnesses, which may compel individuals to engage in salient health related behaviors to cope with the threat, and beliefs about actual participation in health-related behaviors. Specifically, illness beliefs are expected serve as distal predictors of behaviors relevant to coping with illness threat, a theoretically-consistent effect that has not only been corroborated by research showing relations between illness representations and coping behaviors across multiple conditions, but also in laboratory research demonstrating that activating cognitive representations of illness through priming [16,39] leads to the activation of related behavioral responses for the illness [40]. Beliefs about behaviors derived from social cognitive models should be more proximal predictors of behavior given the correspondence and specificity of the beliefs to the behavior themselves and the measures used to tap them [41][42][43].…”
Section: About Illnesses and Beliefs About Behaviorsmentioning
confidence: 91%
“…The model is also evolving, encompassing additional constructs and processes that more effectively and comprehensively explain the processes by which patients' make sense of health threats and regulate their responses (e.g., Benyamini & Karademas, 2019;Cameron et al, 2005b;Durazo & Cameron, 2019;Hagger, Koch, et al, 2017;Karademas et al, 2011;Leventhal et al, 2016;Moss-Morris, 2013;Orbell et al, 2006;Orbell et al, 2015;Orbell & Phillips, 2019;Phillips et al, 2013). Many of these additions represent formal specification of original proposals, while others seek to extend the model to increase its scope and predictive validity.…”
Section: Extended Modelmentioning
confidence: 99%
“…Environmental context is also likely to impact upon illness identification in important ways. Orbell, Henderson, and Hagger (2015) showed that priming the common cold rendered concepts related to the cold more accessible when the common cold was 'in season'. If exposure to illness primes in the environment increases accessibility of a particular illness identity, people are more likely to rapidly detect, label, and act to manage symptoms they experience.…”
Section: Future Directionsmentioning
confidence: 99%
“…Priming and context effects may also be relevant to promotion of positive management of diseases such as hayfever or asthma, where prophylactic medication use is recommended. Orbell et al (2015) showed that even if an individual is not experiencing symptoms and 'seasonality' is low, priming might activate illness schema in the absence of symptoms and impact upon the timely use of preventive medications. Interventions that alter the perceived environment might therefore promote illness schema activation and preventive medication use.…”
Section: Cognitive Accessibility Of Coping Responsesmentioning
confidence: 99%
See 1 more Smart Citation